2020
DOI: 10.1177/0284185120915596
|View full text |Cite
|
Sign up to set email alerts
|

Is the standard deviation of the apparent diffusion coefficient a potential tool for the preoperative prediction of tumor grade in endometrial cancer?

Abstract: Background The tumor histological grade is closely related to the prognosis of endometrial cancer (EC). The use of the apparent diffusion coefficient (ADC), tumor volume, and MRI-based texture analysis has allowed exciting advances in predicting EC grade before surgery. However, whether this constitutes a simple, convenient, and powerful diagnostic method remains unknown. Purpose To explore the utility of standard deviation (SD) of the ADC (ADCSD) for predicting the tumor grade in patients with EC. Material an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…Previous research has also postulated that ADC images are more effective when attempting to identify tumor properties relative to the use of other morphological images such as T1WI and T2WI ( 35 , 36 ). Recently, some researchers have applied radiomic technology to deeply dig into ADC images and found that they could not only evaluate tumor grading but also predict whether the tumor had metastasised ( 37 , 38 ). This indicates that, acting as important MRI functional images, ADC images may show greater value in radiomic analysis than other sequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has also postulated that ADC images are more effective when attempting to identify tumor properties relative to the use of other morphological images such as T1WI and T2WI ( 35 , 36 ). Recently, some researchers have applied radiomic technology to deeply dig into ADC images and found that they could not only evaluate tumor grading but also predict whether the tumor had metastasised ( 37 , 38 ). This indicates that, acting as important MRI functional images, ADC images may show greater value in radiomic analysis than other sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some researchers have applied radiomic technology to deeply dig into ADC images and found that they could not only evaluate tumor grading but also predict whether the tumor had metastasised (37,38). This indicates that, acting as important MRI functional images, ADC images may show greater value in radiomic analysis than other sequences.…”
Section: Radiomics Can Better Reveal the Histological Difference Of Ec When Compared With Adcmentioning
confidence: 99%
“…The relationship between Ki-67 and ADC is controversial in patients with EC. A study has shown that Ki-67 and ADC are negatively correlated [ 14 ], while another study has indicated that there is no correlation between them [ 22 ]. In this study, we also found that there was no significant correlation between ADC m and Ki-67 SI.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we also found that there was no significant correlation between ADC m and Ki-67 SI. Both the DWI and DKI parameters provide valuable imaging biomarkers for EC diagnosis and the assessment of risk stratification in EC [ 19 22 ]. However, in this study, we found no significant difference in ADC m among different grades of EC, as well as different FIGO stages of EC.…”
Section: Discussionmentioning
confidence: 99%
“…For DCE-MRI, its clinical advantages are mainly to improve the diagnostic efficacy of MRI and dynamically present the specific shape of the tumor; for DWI, its clinical advantages are mainly to distinguish the infiltration status and tumor stage [6]. At present, the advantages and disadvantages of the above two solutions are applied in clinical practice, but there are few reports on comparative studies [7]. Given that, to further compare the diagnostic efficacy of DWI and DCE-MRI in the depth of myometrial invasion, cervical invasion and FIGO staging of patients with EC, patients with EC admitted to our hospital were included as the study subjects.…”
Section: Introductionmentioning
confidence: 99%